Assessment of Paediatricians’ Oral Health Knowledge, Behaviour, and Attitude in the United Arab Emirates - Noora Aburahima; Iyad Hussein; Mawlood Kowash; Anas Alsalami; Manal Al Halabi (International Journal of Dentistry)
Aim. Paediatricians’ oral health knowledge is essential for early detection of disease, appropriate advice, and proper referral. Therefore, this study aimed to evaluate the knowledge, behaviour, and attitude of paediatricians practicing in the United Arab Emirates (UAE) regarding children’s oral health. Study Design. Cross-sectional survey. Methods. A questionnaire consisting of 16 questions was completed after piloting by a sample of randomly selected registered UAE paediatricians. Scores of knowledge (out of 9), behaviour (out of 4), and attitude (out of 3) were calculated. Statistical analysis was performed using Shapiro–Wilk, Mann–Whitney U, and Kruskal–Wallis tests. Statistical significance was set as P<0.05. Results. A total of 185 surveys were completed. Nearly half of the paediatricians (95 (51.4%)) identified the appropriate age for child’s first dental visit; while 88 (47.6%) believed that the appropriate age to start brushing was after the eruption of the primary molars (2-3 yrs), and 132 (71.4%) believed that the ideal time to give sugary snacks is in between meals. 123 (66.5%) participants said that they would prescribe antibiotics to treat local dental sepsis without fever. Experienced paediatricians and those trained in Western countries had significantly better knowledge about oral health (P values 0.040 and 0.031 consecutively). The scores of attitude, behaviour, and knowledge were correlated, and a positive relationship between the scores of knowledge and behaviour was found (r = 0.241, P=0.001) and between scores of attitude and behaviour (r = 0.197, P=0.007). Conclusions. The results demonstrated a general lack of knowledge of oral health aspects by UAE paediatricians. Furthermore, continuous education in the subject is recommended.